Evolutionary Features of Personality Research and Leadership Traits. A Comprehensive Analysis - Antonopoulou, Hera (Technium Business and Management, 2023)
The convergence of evolutionary psychology and personality research provides significant insights into personality traits' adaptive origins and functions. The present study investigates the influence of evolutionary pressures on developing specific personality traits associated with leadership inclinations, focusing on the roles played by survival instincts and social cooperation. Specific heritable characteristics, developed and refined over thousands of years, may have provided individuals with advantages in effectively navigating intricate social structures and adapting to environmental demands, making them well-suited for leadership positions. Through a comprehensive understanding of these evolutionary foundations, we can develop a more nuanced and sophisticated viewpoint regarding leadership qualities' biological and adaptive underpinnings. Incorporating an evolutionary perspective enhances the discussion surrounding the cultivation of leadership skills. It emphasizes the inherent origins of leadership qualities, thereby illuminating their historical importance in the survival of the human species and the advancement of societies. The present research comprehensively analyzes various theoretical frameworks pertaining to personality and its correlation with leadership traits. This study aims to examine personality traits by analyzing a range of research studies and presenting their key findings. Numerous theoretical frameworks and empirical investigations have been dedicated to examining personality, encompassing its defining traits, influential determinants, and developmental dynamics in the context of leadership.